Two short memoirs on the development of Philippine social sciences - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2008)
Two short memoirs are offered on the development of Philippine social sciences related to the contributions of two scholars. The first memoir is on Dr. Vernon W. Ruttan and the UP School of Economics during the 1960s. His contributions to the development of the UP School of Economics and of the Philippine economic profession as remembered here were incidental to his main work as the Chief Economist of the newly founded International Rice Research Institute in Los Banos, the Philippines. The second memoir is about Dr. Loretta Makasiar Sicat, political scientist, and the Philippine Social Science Council during the eventful decade from 1973 to 1984. During this period, the PSSC raised its profile and services and built a home for the social science societies in the country under private auspices with the support of the Philippine government and other major donors.
Keywords: 330; Social Sciences; UP School of Economics; Philippine economics; History of social sciences in the Philippines; Sozialwissenschaft; Dogmengeschichte; Philippinen